Restorativeness of play milieu affordance in a paediatric ward in Nigerian hospital - Wakawa, Usman Bukar (2015)
Illness, medical norms and protocols in hospital ward settings cause stress especially for children. This includes confinement, routine medication and limited space for activities and movement. This causes regressive behaviours which include being fearful, boredom, anxiety and restlessness. As a result, the children functioning such as playfulness involving movement and interaction decreases. This phenomenon is common at paediatric hospital wards in Nigeria. The hospital management focus is more on the pathogenic treatment which deals with the provision of ward facilities for treatment of ailment and bodily pains. Thus, no consideration is given to children psychological wellbeing using a holistic approach involving salutogenic treatment with features and interaction in a setting. Therefore, this research employs a salutogenic concept to investigate the benefits of loose play items on children health restoration. Loose play items means moveable materials that children can use in their play. This was experimented with early and middle childhood paediatric patients aged 3 to 12 years. The study was conducted at Abubakar Tafawa Balewa University Teaching Hospital Bauchi with hospitalized children (n=17), (n=10) in control ward and (n=7) in an experiment ward and with (n=25) caregivers. The approach to the conduct of the research was phenomenological. The data were elicited through children’s responses which include their physical, social and cognitive functioning. The data were gathered using video recordings, photographs, Analytical Hierarchy process judgemental scale questionnaire, and interview with caregivers and children's drawings. The analysis was carried out using interpretive content analysis and Expert Choice 11. The analysis indicates various levels of affordances such as sitting alone, feeding and fear of routines that added stress in the control ward. While the experiment ward indicates that the play milieu afforded play, interaction, and movement space that reduces stress and promote children’s functioning, physically, socially and cognitively, leading to restoration. The finding confirms the theories used as research underpinning, theoretical framework and it is consistent with findings in related studies. Therefore, irrespective of different geographical location, country and culture, the restorative benefits of the play milieu can be universally applied in children hospital setting.